2010
DOI: 10.1128/aem.02516-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Multiresistant Salmonella Isolates Capable of Subsisting on Antibiotics

Abstract: This study assessed the ability of Salmonella (572 isolates) to subsist on 12 different antibiotics. The majority (11/12) of the antibiotics enabled subsistence for at least 1 of 140 isolates. Furthermore, 40 isolates were able to subsist on more than one antibiotic. Antibiotic resistance and antibiotic subsistence do not appear to be equivalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Limitation of bacterial growth is most commonly considered to result from nutrient deficiency; however, growth can also be influenced by diverse compounds that are inhibitory when abundant but serve as nutrients at lower concentrations (Abbott, 1973;Kunz et al, 1992;Alvarez et al, 2009;Barnhill et al, 2010). Organic acids, which are key intermediates in global carbon cycles (McInerney et al, 2009), exemplify this paradox in both natural and applied settings (Lee et al, 1976;Louis et al, 2007;Sousa et al, 2009;Huang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Limitation of bacterial growth is most commonly considered to result from nutrient deficiency; however, growth can also be influenced by diverse compounds that are inhibitory when abundant but serve as nutrients at lower concentrations (Abbott, 1973;Kunz et al, 1992;Alvarez et al, 2009;Barnhill et al, 2010). Organic acids, which are key intermediates in global carbon cycles (McInerney et al, 2009), exemplify this paradox in both natural and applied settings (Lee et al, 1976;Louis et al, 2007;Sousa et al, 2009;Huang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Soil bacteria from the orders Pseudomonadales and Burkholderiales have also been isolated based on their capacity to grow on a range of antibiotics as a single carbon source (Dantas et al, 2008). In another environment including clinical and nonclinical samples, Barnhill et al (2011) observed that multi-resistant Salmonella spp. were also able to subsist on antibiotics, highlighting the potential prevalence of the antibiotic subsistence phenotype in a clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…Several members of the bacterial community present in the environment have been identified as reservoirs of antibiotic resistance genes (Riesenfeld et al, 2004;D'Costa et al, 2006). In addition to resistance, recent studies showed that few bacterial species present in soil, seawater and gut microbiota of humans, farm and zoo animals are able to use antibiotics as a sole carbon source, known as the subsistence phenotype (Barnhill et al, 2011, Dantas et al, 2008Dopazo et al, 1988;Xin et al, 2012, chapter 2 of this thesis). In chapter 2, different approaches were implemented to study the genetic determinants involved in this phenotype.…”
Section: Subsistence Phenotype: An Ecological Contextmentioning
confidence: 99%
See 2 more Smart Citations